Faktor -Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Universitas Bengkulu Berkarir di Entitas Syariah - Fani Andrian Permana; Lisa Martiah Nila Puspita (Jurnal Akuntansi, 2016)
The aim of this research is to analyzes the factors that influenceof accounting student University ofBengkulu interest to take a career in sharia entity.The factors are sharia knowledge, work environment and jobmarket considerations.This research is empirical research with quantitative approach which involves the use ofstatistical analysis. This research is using the primary data. The tool used in this research is logistic regression withSPSS software version 16. The results of this research show that the sharia knowledge and work environment has aninfluence on the career in sharia entity, but job market considerations doesn’t influence on the careerin shariaentity.Keywords: sharia entity, sharia knowledge, work environment and job market considerations